Pengaruh Atmosfer Toko, Harga, Variasi Produk, Serta Promosi Terhadap Keputusan Pembelian Toko Ritel Di Masa Pandemi Covid-19 (Studi Kasus Pada Mini Market Alfamart Kota Malang). - Ahmad Luthfi Zamzami; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose of this research is to analyze and explain the influence of store atmosphere, prices, product variations, and promotions on retail store purchasing decisions during the COVID-19 pandemic at the mini market Alfamart in Malang City. The sample in this study were 100 respondents. With the Incidental Sampling technique, the collection of samples met by the researcher by chance, if the person is considered to meet the criteria and is suitable to be used as a data source. By using multiple linear regression analysis, and the results showed the influence of store atmosphere, price, product variations, and promotions had a significant effect on purchasing decisions. The method used in data processing uses a quantitative approach with multiple linear regression analysis tools through the IBM SPSS 16 application program (statistics of product and service solutions). Keywords: store Atmosphere, Prices, Product Variations, Promotions, and Purchasing Decisions